2020
DOI: 10.1051/matecconf/202032102006
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of field assisted sintering technology (FAST) for titanium alloys

Abstract: Field assisted sintering technology (FAST), also known as spark plasma sintering (SPS), is increasingly utilised to process powders/particulates of engineering alloys and metal-based composite materials. FAST is currently extensively used at laboratory scale by research institutes and universities as a rapid and cost‑effective process to consolidate powders. This includes investigating new alloy compositions and material combinations, improving established materials’ properties, and consolidating materials con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The rolled plate is ASTM 256 Ti-6Al-4V Grade 5 in the mill-annealed condition. Two FAST plates of 250 mm diameter were produced using surplus Ti-6Al-4V powder using The University of Sheffield's FCT HP D250 machine, where a large amount of prior research has been carried out into the consolidation of titanium particulates via FAST [13,17,29,30], using a sintering cycle of 30 min dwell time at 1100°C or 950°C with a uniaxial pressure of 35 MPa, with no further heat treatment. The HIPed plate was manufactured by BAE Systems to a proprietary BAE Systems HIP cycle.…”
Section: Plate Processing Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rolled plate is ASTM 256 Ti-6Al-4V Grade 5 in the mill-annealed condition. Two FAST plates of 250 mm diameter were produced using surplus Ti-6Al-4V powder using The University of Sheffield's FCT HP D250 machine, where a large amount of prior research has been carried out into the consolidation of titanium particulates via FAST [13,17,29,30], using a sintering cycle of 30 min dwell time at 1100°C or 950°C with a uniaxial pressure of 35 MPa, with no further heat treatment. The HIPed plate was manufactured by BAE Systems to a proprietary BAE Systems HIP cycle.…”
Section: Plate Processing Routesmentioning
confidence: 99%
“…Alternatively, Hot Isostatic Pressing (HIP) and Field Assisted Sintering Technology (FAST) are direct solidstate consolidation techniques that enable near-net shapes to be produced in one single step, using vacuum or protective atmospheres, with the proven capability to use lower-cost titanium powder and particulate feedstock in the FAST process [10][11][12][13]. HIP is the most common method used for consolidating titanium alloy powders, which are hermetically sealed in a mild or stainless steel can [14].…”
Section: Introductionmentioning
confidence: 99%
“…1). The mass of this fraction is attributed to the sum of the masses of all fractions and multiplied by 100, which is the percentage of this fraction in the sample (%) [19,20]:…”
Section: Main Partmentioning
confidence: 99%
“…Research teams [8] investigated the interaction zone between titanium and aluminium in a composite obtained by immersion and exposure of titanium rods in an aluminium melt. It was [9] found that the heat treatment time and cooling conditions affect the thickness and structure of the transition layer formed as a result of the interaction. The results of [10] show the peculiarity of porosity and coordination number calculations.…”
Section: Literature Reviewmentioning
confidence: 99%